Gene silencing in the aedine cell lines C6/36 and U4.4 using long double-stranded RNA - Bodunrin Omokungbe; Alejandra Centurión; Sabrina Stiehler; Antonia Morr; Andreas Vilcinskas; Antje Steinbrink; Kornelia Hardes (Parasites & Vectors, 2024)
Abstract Background RNA interference (RNAi) is a target-specific gene silencing method that can be used to determine gene functions and investigate host–pathogen interactions, as well as facilitating the development of ecofriendly pesticides. Commercially available transfection reagents (TRs) can improve the efficacy of RNAi. However, we currently lack a product and protocol for the transfection of insect cell lines with long double-stranded RNA (dsRNA). Methods We used agarose gel electrophoresis to determine the capacity of eight TRs to form complexes with long dsRNA. A CellTiter-Glo assay was then used to assess the cytotoxicity of the resulting lipoplexes. We also measured the cellular uptake of dsRNA by fluorescence microscopy using the fluorophore Cy3 as a label. Finally, we analyzed the TRs based on their transfection efficacy and compared the RNAi responses of Aedes albopictus C6/36 and U4.4 cells by knocking down an mCherry reporter Semliki Forest virus in both cell lines. Results The TRs from Biontex (K4, Metafectene Pro, and Metafectene SI+) showed the best complexing capacity and the lowest dsRNA:TR ratio needed for complete complex formation. Only HiPerFect was unable to complex the dsRNA completely, even at a ratio of 1:9. Most of the complexes containing mCherry-dsRNA were nontoxic at 2 ng/µL, but Lipofectamine 2000 was toxic at 1 ng/µL in U4.4 cells and at 2 ng/µL in C6/36 cells. The transfection of U4.4 cells with mCherry-dsRNA/TR complexes achieved significant knockdown of the virus reporter. Comparison of the RNAi response in C6/36 and U4.4 cells suggested that C6/36 cells lack the antiviral RNAi response because there was no significant knockdown of the virus reporter in any of the treatments. Conclusions C6/36 cells have an impaired RNAi response as previously reported. This investigation provides valuable information for future RNAi experiments by showing how to mitigate the adverse effects attributed to TRs. This will facilitate the judicious selection of TRs and transfection conditions conducive to RNAi research in mosquitoes. Graphical Abstract